A graphene based tunable terahertz sensor with double Fano resonances. Issue 29 (7th July 2015) - Zhang, Yuping; Li, Tongtong; Zeng, Beibei; Zhang, Huiyun; Lv, Huanhuan; Huang, Xiaoyan; Zhang, Weili; Azad, Abul K.
Abstract : We propose a tunable terahertz (THz) sensor consisting of a subwavelength graphene disk and an annular gold ring within a unit cell. Abstract : We propose an ultrasensitive terahertz (THz) sensor consisting of a subwavelength graphene disk and an annular gold ring within a unit cell. The interference between the resonances arising from the graphene disk and the gold ring gives rise to Fano type resonances and enables ultrasensitive sensing. Our full wave electromagnetic simulations show frequency sensitivity as high as 1.9082 THz per refractive index unit (RIU) and a figure of merit (FOM) of 6.5662. Furthermore, the sensing range can be actively tuned by adjusting the Fermi level of graphene.